Pengaruh Kompres Hangat terhadap Penurunan Skala Nyeri pada Remaja Putri yang Mengalami Dismenorhoe di SMA Negeri 1 Lohia Kabupaten Muna - Himaniarwati, Himaniarwati; Astiani, Isma (Jurnal Gizi Ilmiah, 2017)
The incidence of menstrual pain in the world is very large. On average, more than 50 percent of women in each country experience it. Based on data on the number of students of SMU Negeri 1 Lohia in 2014, there were 62 Class I students, 55 Class II students and 57 Class III students, so the total number of teenage girls was 174 and 96 experienced menstrual pain, including 15 years old to the age of 15. 17 years. This study aims to determine the effect of warm compresses on reducing pain scale in adolescent girls who experience dysmenorrhea at SMU Negeri 1 Lohia, Muna Regency. This research method uses the Experimental (Pre Experiment) method with a one group pre-post test design. This design only uses one group of subjects, measurements are made before and after treatment. The population is all students or young women of SMU Negeri 1 Lohia who experienced menstrual pain in 2014 with a total of 96 students. The sample consists of 32 cases. The results showed that there was an effect of warm compresses on the menstrual pain scale in SMAN 1 Lohia students with a t value > t table (17,537 > 2,262) or a significant value of p > = 0.05 (0.000 < 0.05). The conclusion is that there is an effect of warm compresses on the menstrual pain scale in SMAN 1 Lohia students in 2014. Suggestions to overcome dysmenorrhea pain is better given a warm compress in giving a warm compress and must pay attention to the correct way of compressing